Country performance against COVID-19: rankings for 35 countries. Issue 12 (21st December 2020) - Jamison, Dean T; Lau, Lawrence J; Wu, Kin Bing; Xiong, Yanyan
Abstract : Objective: To generate rankings of 35 countries from all continents (except Africa) on performance against COVID-19. Design: International time series, cross-sectional analysis. Selected countries: Countries having 5500 or more cases (collectively including 85% of the world's cases) as of 16 April 2020 and that had reached 135 days into their pandemic by 30 July. Main outcome measures: The initial severity and late-pandemic performance of countries can reasonably be ranked by COVID-19 cases or deaths per million population. For guiding policy and informing public accountability during the pandemic, we propose mid-pandemic performance rankings based on doubling time in days of the total number of cases and deaths in a country. Rank orderings then follow. Results: At day 25 into a country's pandemic, cross-country performance variation was modest: in most countries, cumulative deaths doubled in fewer than 5 days. By day 65, and even more so by day 135, great cross-country variation emerged. By day 135, 9 of the 10 top-performing countries on deaths were European, although they were initially hard hit by the pandemic. Thus, rankings change rapidly enough to point to the value of a dynamic indicator. Five countries—Brazil, Mexico, India, Indonesia and Israel—were among the seven poorest performers at day 135 on both cases and deaths. Doubling times for cases and for deaths are positively correlated, but differ sufficiently to point to the value of both indicators. Conclusions: Readily available data support transparently generated rankings of countries' performance against COVID-19 based on doubling times of cases and deaths. It is premature to judge the value of these rankings in practice, but the potential and early experience suggest they might help facilitate identification of good policies and inform judgements on national leadership.